Thermal decomposition mediated Er3+/Yb3+ codoped NaGdF4 upconversion phosphor for optical thermometry. (24th May 2019) - Maurya, S K; Kushawaha, R; Tiwari, S P; Kumar, A; Kumar, K; da Silva, Joaquim C G Esteves
Abstract: Er 3+ /Yb 3+ codoped NaGdF4 upconversion phosphor is synthesized by thermal decomposition route. The phase confirmation of synthesized sample is further confirmed by x-ray diffraction analysis. Particle size and elemental composition of phosphor is analyzed by field emission scanning electron microscopy (FESEM) and energy dispersive x-ray (EDX), respectively. The upconversion emission is measured by exciting the sample with 976 nm diode laser source. The fluorescence intensity ratio (FIR) of two close levels H 1 1 / 2 2 and S 3 / 2 4 is taken into account to study thermometry ability of sample for the temperature range of 301–506 K at a constant laser power (17.60 W cm −2 ). The sensor sensitivity of phosphor is found to 5.107 × 10 −3 K −1 at 301 K.